PHOTO ANALYSIS TOWARDS INDONESIAN TRAVEL BLOGGER TO DETERMINE PHOTO TREND AND TRAVEL BLOGGER BEHAVIOUR IN INTAGRAM - Jayawisnuwardhana, Ramadhan Syah Aditya; Iskandar, Budi Permadi (Journal of Business and Management, 2017)
Abstract. It is undeniable that social media development is currently at its peak. Instagram is one of the fastest growing social media, reaching 400 million users since its launch in October 2010. Instagram became very popular with the public because it displays visual images in the form of photos or videos that attract more attention from users of social media than just writing. Travel blogger is one type of Instagram users are mostly found in Instagram. Given the development of the world of tourism is increasing from year to year, the growth of travel bloggers as one of the triggers of the growth of tourism is an interesting activity to be studied in social media. Travel bloggers usually use Instagram as the main social media linked to their own blogs. Some companies engaged in the field of tourism using travel bloggers services to promote their business activities through Instagram travel blogger account. Travel bloggers in Instagram selected as a media campaign of his business activities because it is considered to have popularity in social media which perfomance is continuing to rise. Apart from side activities as a promotional container for several companies, travel bloggers also act as social media manager and marketers of their own accounts. The purpose of this research is to describe the strategy of 8 travelblogger Instagram account originating from Indonesia. The framework of the photo-making strategy and the management of the number of photo postings are submitted based on the analysis of the photo content that has been done from the sample accounts. Photo analysis is emphasized because the main product of blogger travel lies indeed in the way photos are produced. Photos are more visible visual subject and can not be overstated by writing language. The analysis of growth follower is done to know the making of photo contents most possible to attract user interest instagram and in accordance with current trend. The theories on the aspect of the photo are used to translate the characteristics of the photos uploaded by the sample accounts. The expected result of this strategy is the loyal attitude of the follower and the growing growth of Instagram travelblogger account community from Instagram users' interest in the blogger's travel account.Keywords: social media, instagram, content analysis, photography, follower growth, travel blogger